Surface electromyographic activities of upper body muscles during high-intensity cycle ergometry - McCormick, M. C.; Watson, H.; Simpson, A.; Kilgore, L.; Baker, J. S. (Research in Sports Medicine, 2014)
The aim of this study was to investigate upper body muscle activity during a 30 s Wingate test. Eighteen physically active participants performed a Wingate test while muscle activity was recorded from the brachioradialis (BR), biceps brachii (BB), triceps brachii (TB) and upper trapezius (UT). Measurements were obtained at rest, during a function maximal contraction (FMC) and during the 30 s Wingate test, whilst participants were positioned in a seated position on the cycle ergometer. All muscles were significantly active for the duration of the test. When normalized as a %FMC no differences in activity were found between muscles. Across the 30 s, power output was found to significantly decrease, whereas no changes were found in upper body muscle activity. All muscles investigated were active during the Wingate test and therefore confirmed previous findings that the upper body significantly contributes to power profiles obtained during high intensity cycle ergometry in addition to its role in stabilizing the body.